2020
DOI: 10.1101/2020.06.07.138297
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Ozone nanobubble treatment effectively reduced pathogenic Gram positive and negative bacteria in freshwater and safe for tilapia

Abstract: 19High concentrations of pathogenic bacteria in water usually results in outbreaks of bacterial 20 diseases in farmed fish. Here, we explored the potential application of an emerging nanobubble 21 technology in freshwater aquaculture. Specifically, we aimed to determine if this technology was 22 effective at reducing the concentration of pathogenic bacteria in the water, and to assess whether 23 it was safe for fish. An ozone nanobubble (NB-O3) treatment protocol was established based on 24 examination of nano… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…Notably, the findings of our investigation revealed that better bacterial antigen uptake into the gill tissues after 3 and 6 h immunization is achieved with fish in the vaccinated group that received a pre-treatment with NB-O3 (NB-O3-VAC) compared with fish in the AT-VAC group. It is possible that ozone nanobubbles in the NB-O3-VAC groups activated innate immune system, which modulated immune cells in response to infections [25][26][27]. When these innate immune cells are stimulated, they perform several response mechanisms to antigens, including phagocytosis, degranulation, and production of cytokines, which may trigger and/or recruit other leukocytes (e.g., neutrophils, macrophages, and dendritic cells) to the fish gills, and it is highly tempting to speculate that pre-treatment with NB-O3 might cause a temporary disruption of epithelial cells, leading to reducing barrier, increasing antigen uptake, and producing a greater immune response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, the findings of our investigation revealed that better bacterial antigen uptake into the gill tissues after 3 and 6 h immunization is achieved with fish in the vaccinated group that received a pre-treatment with NB-O3 (NB-O3-VAC) compared with fish in the AT-VAC group. It is possible that ozone nanobubbles in the NB-O3-VAC groups activated innate immune system, which modulated immune cells in response to infections [25][26][27]. When these innate immune cells are stimulated, they perform several response mechanisms to antigens, including phagocytosis, degranulation, and production of cytokines, which may trigger and/or recruit other leukocytes (e.g., neutrophils, macrophages, and dendritic cells) to the fish gills, and it is highly tempting to speculate that pre-treatment with NB-O3 might cause a temporary disruption of epithelial cells, leading to reducing barrier, increasing antigen uptake, and producing a greater immune response.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous investigations, ozone nanobubbles were found to be efficient in reducing bacterial concentrations in water and upregulating the innate immune system of fish, resulting in increased fish survival during pathogenic infections. When Nile tilapia were infected with a pathogenic multidrugresistant Aeromonas hydrophila, they displayed a higher survival rate when exposed to treatments with ozone nanobubbles (NB-O3) [25][26][27]. Given the stimulation of the innate immune system in the treated groups, we hypothesized that this technology might improve the efficacy of immersion vaccines.…”
Section: Introductionmentioning
confidence: 99%
“…While oxygen, nitrogen, and air are the most common types of gases studied as nanobubbles (NBs), research with ozone NBs is still emerging: (i) remediation of sludge, sediments, and groundwater, (ii) removal of micropollutants, (iii) reduction of bacterial pathogens, and (iv) antimicrobial effectiveness for fresh vegetables . Ozone readily reacts with organic and inorganic compounds in water, and it has been widely used as an oxidant and/or disinfectant in water and wastewater treatment.…”
Section: Introductionmentioning
confidence: 99%